Factors influencing farmers in Cameron Highlands to use insecticide in cabbage cultivation - M., Zurina; Mohd. Noor, Mohd Roff; Asmuni, Azizan; Abd Ghani, Idris (IDOSI Publications, 2015)
The alarming negative effects of insecticide used in farming have caused growing concerns by many people. Due to that, various strategies were established to curb the overuse of insecticide, particularly on cabbage cultivation in Cameron Highlands, which is one of the major vegetable producing regions in Malaysia. Unfortunately, the rates of insecticide use remain highly variable. It is the responsibility of the government to shoulder and tackle this problem effectively, especially in finding out the main reasons why insecticide is preferable as the main insect pest control management. This study employed Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM) to understand farmers’ specific attitudes (SA), subjective norms (SN), perceived behavioural control (PBC) and past behavior (PB) towards insecticides use in Cameron Highlands. Simple random sampling procedure was used in selecting 370 cabbage farmers for the study. Five-point Likert scale questionnaires were used to collect data. The data was collected through survey interviews and was analyzed using inferential statistic (correlation and regression). Results of the analysis showed a significant relationship between SA, SN, PBC, PB and the farmers’ intention to apply insecticide in the coming season. PBC was the most important influential factor for behavioural intention, followed by PB, SA and NS.